2015
DOI: 10.1159/000380989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bergamot (<b><i>Citrus bergamia</i></b> (Risso) Wright &#38; Arn.) Essential Oil Aromatherapy on Mood States, Parasympathetic Nervous System Activity, and Salivary Cortisol Levels in 41 Healthy Females

Abstract: Background: Bergamot essential oil (BEO) is commonly used against psychological stress and anxiety in aromatherapy. The primary aim of the present study was to obtain first clinical evidence for these psychological and physiological effects. A secondary aim was to achieve some fundamental understanding of the relevant pharmacological processes. Methods: Endocrinological, physiological, and psychological effects of BEO vapor inhalation on 41 healthy females were tested using a random crossover study design. Vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 23 publications
2
56
0
7
Order By: Relevance
“…A recently conducted double-blinded, randomized, controlled clinical trial study on aromatherapy has suggested that citrus oil is good in relieving the first stage labor pain. It is effective in controlling the nausea and vomiting along with its mood elevating properties [58][59][60] .…”
Section: Lemonmentioning
confidence: 99%
“…A recently conducted double-blinded, randomized, controlled clinical trial study on aromatherapy has suggested that citrus oil is good in relieving the first stage labor pain. It is effective in controlling the nausea and vomiting along with its mood elevating properties [58][59][60] .…”
Section: Lemonmentioning
confidence: 99%
“…Several clinical studies on aromatherapy with BEO, in combination with other essential oils, have shown promising results: anxiety and stress reduction, anti‐depression, pain relief, and blood pressure and heart rate reduction. Further human studies with BEO inhalation alone have also shown significant effects on anxiety reduction (Watanabe et al , ), depression reduction (Watanabe et al , ), and blood pressure (Chang and Shen, ; Ni et al , ) and heart rate reduction (Chang and Shen, ; Ni et al , ). In addition, BEO has minimal side effects, if any (Navarra et al , ), suggesting BEO inhalation may have potential therapeutic benefits including improving overall mental health and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al . noted that during emotional improvement after relaxation, cortisol levels are also reduced. Because cortisol levels rise during stress, this hormone is sometimes found to be associated with negative affect .…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Watanabe et al . reported a link between essential oil aromatherapy, mood states and salivary cortisol concentration in 41 healthy females. In a current research project on 35 female subjects inhaling the odour of saffron volatile oil for 20 min led to a decrease in both cortisol and anxiety level .…”
Section: Discussionmentioning
confidence: 96%